Financial Feasibility of a Crab Fishing Business in Pajukukkang Village, Bontoa District, Maros Regency - Adryan Mahendra Alfian; Amiluddin Amiluddin (PONGGAWA : Journal of Fisheries Socio-Economic, 2025)
This study aims to analyze the financial feasibility of the blue swimming crab fishing business in Pajukukkang Village, Bontoa District, Maros Regency. The analysis was conducted by calculating profit, the revenue-to-cost ratio (R/C Ratio), and the payback period (Payback Period). The research method used was quantitative descriptive with data collection techniques through observation, interviews, and literature study. There were 112 crab fishermen, so 20% of the population was taken as the research sample, resulting in a sample of 23 crab fishermen. The results show that business profits vary depending on the season. During the peak season, profits reach IDR 11,454,056, while during the transition season, profits drop to IDR 4,300,664. The feasibility analysis using the R/C Ratio shows values of 2.38 in the peak season and 1.77 in the transition season, indicating that the business is viable. Additionally, the Payback Period analysis reveals that the investment can be recovered within 2.75 years or approximately 2 years and 9 months. Based on these findings, it can be concluded that the blue swimming crab fishing business in Pajukukkang Village has good financial prospects and is feasible for further development.